Unveiling the multifaceted role of toll-like receptors in immunity of aquatic animals: pioneering strategies for disease management - Ghani, Muhammad Usman; Chen, Junfan; Khosravi, Zahra; Wu, Qishu; Liu, Yujie; Zhou, Jingjie; Zhong, Liping; Cui, Hongjuan (Frontiers in Immunology, 2024)
The pattern recognition receptor (PRR), which drives innate immunity, shields the host against invasive pathogens. Fish and other aquatic species with poorly developed adaptive immunity mostly rely on their innate immunity, regulated by PRRs such as inherited-encoded toll-like receptors (TLRs). The discovery of 21 unique TLR variations in various aquatic animals over the past several years has sparked interest in using TLRs to improve aquatic animal's immune response and disease resistance.This comprehensive review provides an overview of the latest investigations on the various characteristics of TLRs in aquatic animals. It emphasizes their categorization, insights into 3D architecture, ligand recognition, signaling pathways, TLRs mediated immune responses under biotic and abiotic stressors, and expression variations during several developmental stages. It also highlights the differences among aquatic animals' TLRs and their mammal counterparts, which signifies the unique roles that TLRs play in aquatic animal's immune systems. This article summarizes current aquaculture research to enhance our understanding of fish immune systems for effective aquaculturerelated disease management.